A ring of grids: a giant spin-crossover cluster. Issue 79 (13th September 2021) - Shiga, Takuya; Tachibana, Minami; Sagayama, Hajime; Kumai, Reiji; Newton, Graham N.; Oshio, Hiroki; Nihei, Masayuki
Abstract : Mononuclear and icosanuclear spin-crossover complexes, [Fe] and [Fe20 ], were synthesized. [Fe] has a bis-chelate structure, while [Fe20 ] has a ring-shape structure comprising four [2 × 2] grid moieties and four mononuclear units. Abstract : Mononuclear and icosanuclear spin-crossover complexes, [Fe II (HL)2 ](BF4 )2 (1 ) and [FeII20(L)24 ](BF4 )16 (2 ), were synthesized using an asymmetric multidentate ligand (HL). 1 has a bis-chelate structure with two protonated ligands, while 2 has a ring-shape structure comprising four [2 × 2] grid moieties and four mononuclear units.